Sono, qualidade de vida e depressão em mulheres no pós-tratamento de câncer de mama - Rafihi-Ferreira, Renatha El; Pires, Maria Laura Nogueira [UNESP]; Soares, Maria Rita Zoéga (Universidade Federal do Rio Grande do Sul (UFRGS), Pós-Graduação em Psicologia, 2012)
Este trabalho investigou a qualidade de sono de mulheres com câncer de mama e suas relações com qualidade de vida e depressão. Cinqüenta mulheres com câncer de mama (grupo clínico) e cinqüenta controles responderam um questionário médico-demográfico e ao instrumento Pittsburgh Sleep Quality Index. O grupo clínico também respondeu aos instrumentos Quality of Life Cancer-Survivor e Brief Zung Self-Rating Depression Scale. Verificou-se que mulheres com câncer tinham significativamente mais queixas de nictúria, calor e despertares noturnos. O grupo clínico com má qualidade do sono apresentou comprometimento na qualidade de vida e mais sintomas de depressão. em geral, a qualidade de sono em mulheres com câncer de mama pode predizer a qualidade de vida e o bem estar psicológico.

This study investigated the sleep quality of women with breast cancer and their relationship with quality of life and depression. Fifty women with breast cancer (clinical group) and a control group of other 50 women without the disease answered a clinical-demographic questionnaire and the Pittsburgh Sleep Quality Index. The clinical group also completed the Quality of Life Cancer-Survivor and the Brief Zung Self-Rating Depression Scale questionnaires. It was found that women with breast cancer had significantly more complaints of nocturia, heat and nighttime awakenings. The clinical group with poor quality of sleep reported impaired quality of life and more symptoms of depression. In general terms, sleep quality in women with breast cancer can predict their quality of life and psychological well-being.
Sleep, quality of life and depression in women in breast cancer post-treatment
Keywords: Câncer de mama; insônia; qualidade de vida; depressão; Breast cancer; insomnia; quality of life; depression